2018
DOI: 10.1037/pri0000065
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between trainee therapists’ and clients’ initial expectations and actual treatment duration and outcomes.

Abstract: The purpose of this study was to examine the relationship between trainee therapists’ and clients’ duration and outcome expectations and actual treatment duration and outcomes for clients. Eleven therapists-in-training completed measures of duration and outcome expectations for clients in general at the start of the study. After the intake sessions, trainee therapists and their clients (N = 34) completed the same expectation questions applied to the specific case. Results indicated that clients’ expectations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Thus, it is plausible that each dyad member's OE contributes in unique ways to their own and their partner's experience of the therapeutic relationship and, ultimately, to the patient's treatment outcome. Supporting this perspective, although the vast majority of OE studies have focused exclusively on patient OE, the few exceptions all found that more optimistic therapist OE (for a specific patient's outcome) was associated with greater patient improvement (Connor & Callahan, 2015;Joyce et al, 2003;Meyer et al, 2002;Swift, Derthick, & Tompkins, 2018). Moreover, there is some evidence that greater therapist OE is associated with more positive patient-perceived alliance quality (Meyer et al, 2002).…”
mentioning
confidence: 99%
“…Thus, it is plausible that each dyad member's OE contributes in unique ways to their own and their partner's experience of the therapeutic relationship and, ultimately, to the patient's treatment outcome. Supporting this perspective, although the vast majority of OE studies have focused exclusively on patient OE, the few exceptions all found that more optimistic therapist OE (for a specific patient's outcome) was associated with greater patient improvement (Connor & Callahan, 2015;Joyce et al, 2003;Meyer et al, 2002;Swift, Derthick, & Tompkins, 2018). Moreover, there is some evidence that greater therapist OE is associated with more positive patient-perceived alliance quality (Meyer et al, 2002).…”
mentioning
confidence: 99%
“…There is increasing evidence that patients do have preferences for psychotherapy or pharmacotherapy (McHugh, Whitton, Peckham, Welge, & Otto, ), cognitive behavioral or interpersonal psychotherapy, individual or group therapy, brief or long‐term psychotherapy (Swift, Derthick, & Thompkins, ). As awareness of psychological treatments grows, prospective patients may want to compare different treatments before choosing a preferred psychotherapy approach.…”
Section: How Do Ests Mitigate Patient Anxieties?mentioning
confidence: 99%
“…In that study, trainees were found to be optimistic but inaccurate in their expectations pertaining to both attrition risk and likelihood of client improvement. A more recent study by Swift, Derthick, and Tompkins (2018) has provided greater understanding of that effect. Following intake, both practicum therapists and clients completed a measure of expectancies concerning their work together.…”
Section: Training To Thwart Attrition: the Role Of Intakementioning
confidence: 99%